Ocular changes in patients on maintenance hemodialysis - Naseem, Azhar; Rustam, Naeem; Sabir, Omer; Riaz, Muhammad Mohsin; Anjum, Khalid Mahmood; Tarif, Nauman (Pakistan Journal of Kidney Diseases, 2021)
BACKGROUND: Patients with end-stage renal disease (ESRD) are at risk for development of eye disease; in the conjunctivae, cornea, retina, and macula, related to the comorbid conditions as well as to the unique effects of hemodialysis and the uremic state. We performed a cross sectional study to document the frequency of ocular changes in patients of end stage renal disease (ESRD) on maintenance hemodialysis. METHODOLOGY: Patients with chronic kidney disease on hemodialysis for more than 6 months were enrolled in the study. Visual acuity was done at bedside with snellen chart at 6 meter distance. Torch light, slit lamp and direct ophthalmoscopy was also done using hand held direct ophthalmoscope. The findings were documented by the ophthalmology consultant. RESULTS In our study, out of 72 cases of end stage renal disease, 26.39%(n=19) were between 18-50 years of age while 73.61% (n=53) were between 51-85 years of age, mean+sd was calculated as 57.03+9.4 years, 56.94% (n=41) were male and 43.06% (n=31) were females, frequency of ocular changes in patients of ESRD on hemodialysis was recorded as 45.83% (n=33) for hypertensive retinopathy, 4.17%(n=3) had conjunctival calcification and 44.44%(n=32) had cataracts. CONCLUSION Frequency of ocular changes is higher among patients of ESRD on hemodialysis in our targeted population, however, some other multi-center studies are required to validate our results.